Explicating Cues: A Typology for Understanding Emerging Media Technologies. Issue 1 (17th December 2019) - Xu, Kun; Liao, Tony
Abstract: Cues have long been an important concept in computer-mediated communication (CMC), as several core theories have utilized cues to explain how they get filtered and interpreted through technologies. As computing technologies evolved, other related fields have also adopted cues as a concept for understanding technological interaction. Given the pervasive nature of cues, this article first explicates the concept and creates a typology of cues based on how different fields have studied them. It then examines key differences in how existing theories approach cues and their assumptions behind cues, and further pulls apart the relationship between different cue categories and their potential effects on social presence. Lastly, we explain how researchers could draw on this typology to understand the increasingly multifaceted ways that emerging media technologies present cues and evoke social presence. A clear typology of cues is necessary both to clarify the term and help guide future evolutions of CMC.